A122: Correlation between expression of antigens on tumor cells and recurrent genetic abnormalities in chronic lymphocytic leukemia. Issue 1 (November 2015) - Kolubaeva, S.
Abstract : Background: Tumor cells in chronic lymphocytic leukemia (CLL) usually have the "classic" immunophenotype CD19+, CD5+, CD23+, SmIgdim, CD20dim, FMC7-, CD79b-/dim, CD22-/dim. However, sometimes some deviations in antigenic profile CLL cells are observed such as enhanced expression of CD79b, CD22, SmIg and CD20. The most frequent cytogenetic abnormalities in CLL are trisomy 12 and deletions of 13q14, 13q34, 6q, 11q, and 17p. It is noted that immunophenotypic deviations in CLL often correlate with some of these cytogenetic anomalies. The investigation of the links between the antigens expression and caryotype of CLL cells leads to differential diagnostics and prognosis in CLL. The goal of the investigation is search for the links between immunophenotypic characteristics of CLL cells and their karyotype. Material and methods: Bone marrow and blood cells from 35 CLL patients are investigated. Immunophenotyping was made using flow cytometer "Cytomics F500" (Beckman Coulter) with the use of monoclonal antibodies CD3/CD19/CD45, SmIg κ SmIg λ /CD19, CD5/CD23/CD19, FMC7/CD38/CD19, CD22/CD79b/CD19, CD10/CD20/CD19. For karyotype determination the standard cytogenetic methods and FISH were used. Results: The most frequent deletion in CLL patients was del(13)(q14.3), it was sometimes observed together with (13)(q34) and was found in18 patients (51% of all examined patients). 56% (10/18) of patients in this group had CLL cells phenotype CD19+, CD5+, CD23+, SmIgdim, CD20dim, FMC7-, CD79b-, CD22- and CD38-. Weak (dim) expression of CD79b antigen (in 24–92% of cells) was found in 39% (7/18) of patients with del(13)(q14.3), and expression of CD38 (in 22–86% of cells) – in 17% (3/18). The same phenotype was observed in 2 patients (6%) having only del(13)(q34), in one patient (3%) with (13)(q34) trisomy and in 6 patients (17%) with normal karyotype 46, XY. Trisomy 12 was found in 14% (5/35) of explored CLL patients. The immunophenotype of CLL cells in this group was very different with the previous group. All patients (100%) with trisomy 12 had CLL cells with expression of CD79b (94.2% of cells), CD22 (54–94.6% of cells), CD38 (31.1–99.3% of cells). Additionally 2 of 5 patients (40%) had CLL cells with more bright (dim to mod) CD20 expression and 1 patient (20%) had cells with bright expression of CD79b (in 94.2% of cells). The same phenotype was registered in one patient with del(6q23), comprising CD78b+ (in 97.8% of cells), CD22+ (in 62.6% of cells) and CD38+ (in 32.5% of cells). In 2 patients (6%) with del (11)(q23) expression of CD79b (in 47.3–44.8% of cells) and CD38 (in 35.3–64.4% of cells). Conclusion: Expression of CD79b, CD22, CD38 is the main feature of cells with recurrent genetic injuries. Immunophenotype without expression of CD79b, CD22, CD38 in most cases differentiates CLL patients with del(13)(q14.3), del (13)(q34), (13q)(34) trisomy and with normal karyotype. Coexpression in the most of the cells of the three antigens CD79b, CD22, CD38 and more bright expression of CD20 proposes trisomy 12 or del(6q). Partial expression of CD79b and CD38 may correlate with del(11)(q23).